Hubungan Antara Lama Kontak Dengan Kejadian Dermatitis Kontak Akibat Kerja Pada Pekerja Bengkel Kendaraan Bermotor Di Kecamatan Kartasura Kota Sukoharjo - Kusworo, Nur Seta Ridho; , dr. Nurrachmat Mulianto, M.Sc., Sp.K.K; , dr. Ratih Pramuningtyas, Sp.KK (2015)
Background : Occupational contact dermatitis (OCD) is a skin condition caused by work-related exposures. Occupational contact dermatitis accounts for 90% of all cases of work-related cutaneous disorders. It can be divided into irritant contact dermatitis, and allergic contact dermatitis. There are two factors that affect the occurrence of contact dermatitis, which is a exogenous and endogenous factors. duration of contact is one of the exogenous factors on the occurrence of OCD. Objective : To determine the relationship between the duration of contact with the incidence of occupational contact dermatitis on the motor vehicle repair shop workers in the district Kartasura Sukoharjo. Methods : This study uses an analytical observational study with cross sectional design which will be conducted at 60 motor vehicle repair shop workers. Results : Based on the analyze of data that have been obtained by Chi-square test ρ = 0, 037 (ρ < 0,05). Conclusion : There is a relationship between the duration of contact with the incidence of occupational contact dermatitis on the motor vehicle repair shop workers in the district Kartasura Sukoharjo